A structural model with interventions for new Zealand sawn timber production. (1st June 2006) - Luo, Dongwen; Jones, Geoffrey; Dennis, Judith
Abstract : Timber production in New Zealand was privatized in 1987. We examine the effects of this change on the level of New Zealand sawn timber production, and changes in the seasonal pattern, using a state-space model with intervention variables. We describe the formulation and estimation of the state-space model, and show how it can be used to examine both the structural changes around the time of privatization and the gradually evolving seasonal pattern in production. We also show how the model can be used to forecast future production.